2020
DOI: 10.5747/ca.2020.v16.n2.a360
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogênio e Azospirillum brasilense no desenvolvimento inicial da cana-de-açúcar

Abstract: A study was conducted with the objective of investigating the effects of the interaction between the inoculation of the pre-sprouted seedlings with Azospirillum brasilenseand the nitrogen fertilization in topdressing on the development of sugarcane plants(Saccharum officinarum). Pre-sprouted sugarcane seedlings, produced from 3.0 cm long mini-stems of the RB867515 variety, were transplanted 25 days after sprouting into 12 L plastic pots. The treatments were arranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
2
0
2
Order By: Relevance
“…The optimal rate of inoculant containing A. brasilense to be in transplanting sugarcane seedlings based on all the indexes of presprouted seedlings can range from 2 to 3 mL of inoculant per seedling (Tables 2, 3 and 4). These results confirm the evidence previously reported by Gonçalves et al (2020), which showed that the use of 4 mL per seedling of inoculant containing A. brasilense caused phytotoxic effects on the plant development of sugarcane genotype RB867515 up to 60 days after transplanting. This evidence shows the importance of establishing the ideal inoculant rate to be applied since high inoculant rates cause phytotoxic effects.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The optimal rate of inoculant containing A. brasilense to be in transplanting sugarcane seedlings based on all the indexes of presprouted seedlings can range from 2 to 3 mL of inoculant per seedling (Tables 2, 3 and 4). These results confirm the evidence previously reported by Gonçalves et al (2020), which showed that the use of 4 mL per seedling of inoculant containing A. brasilense caused phytotoxic effects on the plant development of sugarcane genotype RB867515 up to 60 days after transplanting. This evidence shows the importance of establishing the ideal inoculant rate to be applied since high inoculant rates cause phytotoxic effects.…”
Section: Resultssupporting
confidence: 92%
“…These bacteria can promote the shoot growth and induce the emission of new leaves on the plants (SERNA-COCK et al, 2011;MOURA et al, 2019;GONÇALVES et al, 2020). This increase in the number of leaves makes the plants more efficient in the use of solar radiation and, consequently, there is an increase in the photosynthesis rate and the accumulation of dry matter of the plants (OLIVEIRA et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentre os indivíduos capazes de realizar a conversão do N2 atmosférico em formas assimiláveis pelas plantas (NH 3 ), o gênero Azospirillum está entre os principais grupos de interesse agronômico devido sua capacidade de atuar mediando a fixação biológica de nitrogênio para as plantas (Moura et al, 2019). Nesse sentido, Gonçalves et al (2020) estudaram o efeito da interação entre a inoculação de mudas pré-brotadas com Azospirillum brasilense (4 ml do inoculante comercial AzoTotal®) e diferentes doses de adubação nitrogenada em cobertura (0, 30, 60, 90 e 120 mg dm -3 ) no desenvolvimento da cana de açúcar. Portanto, os autores observaram que a associação dose + inoculação teve caráter positivo, onde, foi notável o incremento linear da altura das plantas, diâmetro de colmos, número de folhas por planta, número de perfilhos e matéria seca.…”
Section: Manejo De Macro E Micronutrientesunclassified
“…Além da correção de acidez do solo, com aplicação de calcário ou escória de siderur-gia, a produtividade da cana-de-açúcar está diretamente relacionada à adubação nitrogenada, pois o N é um dos nutrientes limitantes à produtividade e a longevidade das soqueiras de cana- de-açúcar (BARTH et al, 2020;GONÇALVES et al, 2020 Para estabelecer as doses de nitrogênio, tomou-se como padrão a dose 120 kg ha -1 de N, indicada para a cana-soca, com meta de produtividade maior que 100 t ha -1 no estado de São Paulo (SPIRONELLO et al, 1997).…”
Section: Introductionunclassified